Characteristics of low-acuity paediatric emergency department consultations in two tertiary hospitals in Switzerland: a retrospective observational study - Mario Gehri; Claudia E Kuehni; Kristina Keitel; Joan-Carles Suris; Manon Jaboyedoff; Carl Starvaggi; Rachel Pellaton (BMJ Publishing Group, 2021)
Background Low-acuity paediatric emergency department (PED) visits are common in high-income countries and are an increasing burden for the healthcare system and quality of care. Little is known about low-acuity PED visits in Switzerland. This study shows frequency and characteristics of such visits in two large PEDs in German-speaking and French-speaking regions of Switzerland.Methods We conducted a retrospective observational study in the PED of two Swiss tertiary care hospitals, Bern and Lausanne. We extracted standardised administrative and medical data from the clinic information system for all PED visits of children aged 0-17 years from January to December 2018. We defined low-acuity visits as those meeting all of the following criteria: (1) triage category 4 or 5 on the Australasian Triage Scale, (2) no imaging or laboratory test performed and (3) discharge home. We used a binary multiple logistic regression model to identify factors associated with low-acuity visits.Results We analysed 53 089 PED visits. The proportion of low-acuity visits was 54% (95% CI 53% to 54%, 28 556 visits). Low-acuity visits were associated with age younger than 5 years (adjusted OR, aOR 1.87, 95% CI 1.81 to 1.94), living within a 5 km radius of PED (aOR 1.27, 95% CI 1.22 to 1.32), and after hour presentations (weekends: aOR 1.14, 95% CI 1.10 to 1.18, nights: aOR 1.10, 95% CI 1.23 to 1.36).Conclusion Low-acuity visits are frequent in our PEDs and associated with younger age and convenience factors (proximity of residency and after hour presentation), pointing to a high demand for paediatric urgent care services in Switzerland not currently covered by the primary healthcare system.